Trade Liberalization and the Politics of Financial Development - Braun, Matias (World Bank, Washington, DC, 2012)
A well developed financial system enhances competition in the industrial sector by allowing easier entry. The impact varies across industries, however. For some, small changes in financial development quickly induce entry and dissipate incumbents' rents, generating strong incentives to oppose improvement of the financial system. In other sectors incumbents may even benefit from increased availability of external funds. The relative strength of promoters and opponents determines the political equilibrium level of financial system development. This may be perturbed by the effect of trade liberalization in the strength of each group. Using a sample of 41 trade liberalizers the authors conduct an event study and show that the change in the strength of promoters vis-a-vis opponents is a very good predictor of subsequent financial development. The result is not driven by changes in demand for external funds, or by the success of the trade policy. The relationship is mediated by policy reforms, the kind that induces competition in the financial sector, in particular. Real effects follow not so much from capital deepening but mainly through improved allocation. The effect is stronger in countries with high levels of governance, suggesting that incumbents resort to this costly but more subtle way of restricting entry where it is difficult to obtain more blatant forms of anti-competitive measures from politicians.